2018
DOI: 10.1002/hbm.24473
|View full text |Cite
|
Sign up to set email alerts
|

Regional multimodal relationships between tau, hypometabolism, atrophy, and fractional anisotropy in atypical Alzheimer's disease

Abstract: Alzheimer’s disease (AD) can present with atypical clinical forms where the prominent domain of deficit is not memory, i.e. atypical AD. Atypical AD patients show cortical atrophy on MRI, hypometabolism on [18F]fluorodeoxyglucose (FDG) PET, tau uptake on [18F]AV-1451 PET, and white matter tract degeneration on diffusion tensor imaging (DTI). How these disease processes relate to each other locally and distantly remains unclear. We aimed to examine multimodal neuroimaging relationships in individuals with atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 51 publications
9
48
0
Order By: Relevance
“…We found that SUVRs in the temporal ( R = −0.530, P = 0.020), parietal ( R = −0.637, P = 0.003), and occipital ( R = −0.567, P = 0.011) lobes correlated negatively between [ 18 F]-APN-1607 and [ 18 F]-FDG uptakes, with a trend toward negative correlation in the frontal lobe ( P = 0.073, R = −0.421). These findings were consistent with results disclosed using other tau tracers [[ 18 F]-AV-1451 ( Gordon et al, 2019 ; Sintini et al, 2019 ) and [ 18 F]-THK5351 ( Baghel et al, 2019 )]. Previous stereological and non-stereological quantitative post-mortem studies of cerebral cortex ( Terry et al, 1981 , 1987 ; Cras et al, 1995 ; Schwab et al, 1998 , 1999 ; Bussiere et al, 2002 ; Kril et al, 2002 ) and clinicopathologic studies ( Giannakopoulos et al, 2003 ) reported a close association between NFT counts and neuron loss.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that SUVRs in the temporal ( R = −0.530, P = 0.020), parietal ( R = −0.637, P = 0.003), and occipital ( R = −0.567, P = 0.011) lobes correlated negatively between [ 18 F]-APN-1607 and [ 18 F]-FDG uptakes, with a trend toward negative correlation in the frontal lobe ( P = 0.073, R = −0.421). These findings were consistent with results disclosed using other tau tracers [[ 18 F]-AV-1451 ( Gordon et al, 2019 ; Sintini et al, 2019 ) and [ 18 F]-THK5351 ( Baghel et al, 2019 )]. Previous stereological and non-stereological quantitative post-mortem studies of cerebral cortex ( Terry et al, 1981 , 1987 ; Cras et al, 1995 ; Schwab et al, 1998 , 1999 ; Bussiere et al, 2002 ; Kril et al, 2002 ) and clinicopathologic studies ( Giannakopoulos et al, 2003 ) reported a close association between NFT counts and neuron loss.…”
Section: Discussionsupporting
confidence: 92%
“…Positron emission tomography with [ 18 F]-FDG reveals a characteristic pattern of hypometabolism in temporoparietal cortex and posterior cingulate of AD patients ( Minoshima et al, 1995 ; Kato et al, 2016 ; Hsu et al, 2017 ; Rice and Bisdas, 2017 ; Blazhenets et al, 2019 ). Multimodal studies combining A/T/N biomarkers showed tau deposition as measured by [ 18 F]-AV-1451 ( Sintini et al, 2019 ) or [ 18 F]-THK5351 ( Baghel et al, 2019 ) PET, which correlated with hypometabolism to [ 18 F]-FDG PET and with atrophy, as measured by structural magnetic resonance imaging (MRI) ( Sintini et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior voxel‐level analyses have found different regional patterns of cortical volume loss 42–44 and flortaucipir uptake in the cortex 45–48 between PCA and LPA. The aim of our study was not to identify regional differences between PCA and LPA, and hence we did not repeat these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have demonstrated striking [ 18 F]AV-1451 uptake in patients with AD, with patterns differing with age (Lowe et al, 2018; Pontecorvo et al, 2017; Tetzloff et al, 2018) and across clinical variants (Ossenkoppele et al, 2016; Scholl et al, 2017). Studies have also shown close spatial relationships between tau-PET uptake and grey matter volume in typical and atypical clinical variants of AD (Dronse et al, 2017; Iaccarino et al, 2018; Ossenkoppele et al, 2016; Sintini et al, 2018; Whitwell et al, 2018; Xia et al, 2017) and demonstrated that tau uptake is also related to antecedent rates of volume loss (Das et al, 2018; Gordon et al, 2018). Two studies have investigated longitudinal regional changes in [ 18 F]AV-1451 uptake in AD patients (Harrison et al, 2018; Jack et al, 2018).…”
Section: Introductionmentioning
confidence: 91%